SIKOPE : Pengembangan Sistem Informasi Akuntansi Laboratorium Koperasi - Carolina Lita Permatasari; Dwi Iga Luhsasi (Jurnal Sistem Informasi Akuntansi (JASIKA), 2026)
The purpose of developing a cooperative accounting information system in the cooperative laboratory is to assist students as managers of cooperative laboratories in studying cooperative activities in terms of recording stock of goods and financial reporting to be more effective, efficient, transparent and accountable. The innovations in this cooperative accounting information system are single entry accounting records, automation of financial statement recapitulation calculations, automation of stock calculations when sales occur, easily accessible anytime and anywhere. The output of the inputted report is a print preview to print the report by connecting to the hardware (printer). This research is included in accounting information system development research. The stages used in this research adapt the Pressman Waterfall Model (Communication, Planning, Modeling, Construction, and Deployment). The results of the development research state that the cooperative accounting information system is feasible to implement. This is evidenced by the results of the validation test of material experts, technology experts, and trials to users who are in the very good category. The development of a cooperative accounting information system is needed for cooperative learning and training activities as well as accounting records for students for stock reporting and recording financial reports that are effective, efficient, transparent, and accountable.